(3Gdfeh GddZhj dCHfGFc hYdGLg (B=s Children linguistic competence and treatment - (3GdSjO, EHQGgje LGHQs ((3GdbGgQI (B:s (3GdSQGL ddfTQ hGdJhRjY,s, 2019)
(3JMOK GdGVWQGHGJ GddZhjI YfO GdCWaGd fJjLI dCSHGH HjFjI hfaSjI, hYUHjI, hGdJj jUGHhf HgG bHd GdhdGOI Ch HYOgG ; MjK JYJHQ GdGVWQGHGJ GddZhjI bGSeG eTJQcG Hjf YOO ef aFGJ GdJQHjI GdNGUI(B. (3hjYGfj gDdGA GdCWaGd ef GfNaGV hGVM hedMhX aj bOQGJge GddZhjI, HGdEVGaI Edi GVWQGHGJ dZhjI hJhGUdjI JMO ef bOQGJge Ydi GdJhGUd eY GdBNQjf HTcd aYGd EPG eG bGQfGge Hef jeGKdhfge aj GdYeQ GdRefj, hgPG jMJe YdjfG GdMO ef gPg GdeTcdI HEjLGO ESJQGJjLjGJ YdGLjI hHQGeL JQHhjI(B.s
(3JUeje GdZdGa (B: (3CMeO GdUHGZ(B.s
(3HHdjhLQGajI (B: (3UaMI (B254-255.s
Keywords: (3GdCWaGds -- (3dZIs; (3GdCWaGds -- (3fehs